Evaluation of Physicochemical and Microbiological Properties of Milk Collected from Traditional Sale Centers in Shiraz, Southern Iran - Maryam Esfandiari; Marjan Majdinasab; Raheleh Najafi Seraji; Seyed Mohammad Hashem Hosseini; Mohammad-Taghi Golmakani (International Journal of Nutrition Sciences)
Background: Milk and dairy products have important roles in the human diet. Therefore, quality control and monitoring of the hygiene standards of dairy products during production, transportation, storage, and distribution are of particular importance. Due to the poor sanitary conditions during storage, improper heat treatment, and post-contamination, traditional dairy products can be a good media for the growth of a wide range of microorganismsMethods: This study aimed to evaluate traditional dairy products in Shiraz including 25 samples of raw cow's milk (cold and warm seasons), for significant risk factors. Physical, chemical, and microbial tests were performed according to the national standard of Iran.Results: The trend of changes in fat, solids-non-fat, and freezing point of raw milk samples in cold seasons was more than in hot seasons. In addition, instability against alcohol and somatic cells was higher in warm-season samples. The milk density was unrelated to seasons. The microbial quality of the samples was not within the national standard of Iran, which could be due to improper storage conditions and lack of cold chain control from livestock to supply centers. PCR analysis confirmed the absence of two pathogenic bacteria Escherichia coli O157:H7 and Listeria monocytogenes in raw milk samples.Conclusion: According to the present results, the quality of traditional dairy products distributed in Shiraz is not good. Therefore, having a specialized technical manager for traditional dairy units is essential. Furthermore, more serious and more supervision is needed from livestock to distribution centers by relevant organizations and centers.